Undergraduate and postgraduate programmes in remote sensing at University Technology Malaysia - Seeni Mohd., Mohd. Ibrahim; Hashim, Mazlan (Asian Association on Remote Sesning, 1997)
The Faculty of Geoinformation Science and Engineering at University technology Malaysia has been offering B.Sc programmes in land surveying and poverty management since 1972. However, with the increasing needs for professionals in other fields such as remote sensing, geoinformatics and land administration & development , the Faculty now offers three more new courses, namely :1) B.Sc (Remote sensing ), (2) B.Sc (Geoinformatics), and (3) B.Sc (Land Administration & Development ). The Faculty also has been offering postgraduate programmes related to geomatic engineering, remote sensing, geoinformatics, GPS surveying, hydrography, property management and land administration & development. This paper presents an overview of the undergraduate and postgraduate programmes in remote sensing at the Faculty.